Carbon accumulation in aboveground and belowground biomass and soil of different age native forest plantations in the humid tropical lowlands of Costa Rica - Fonseca, William (2012)
Generic or default values to account for biomass and carbon accumulation in tropical forest ecosystems are generally recognized as a major source of errors, making site and species specific data the best way to achieve precise and reliable estimates. The objective of our study was to determine carbon in various components (leaves, branches, stems, structural roots and soil) of single-species plantations of Vochysia guatemalensis and Hieronyma alchorneoides from 0 to 16 years of age. Carbon fraction in the biomass, mean (±standard deviation), for the different pools varied between 38.5 and 49.7% (±3 and 3.8). Accumulated carbon in the biomass increased with the plantation age, with mean annual increments of 7.1 and 5.3 Mg ha-1 year-1 for forest plantations of V. guatemalensis and H. alchorneoides, respectively. At all ages, 66.3% (±10.6) of total biomass was found within the aboveground tree components, while 18.6% (±20.9) was found in structural roots. The soil (0–30 cm) contained 62.2 (±13) and 71.5% (±17.1) of the total carbon (biomass plus soil) under V. guatemalensis and H. alchorneoides, respectively. Mean annual increment for carbon in the soil was 1.7 and 1.3 Mg ha-1 year-1 in V. guatemalensis and H. alchorneoides. Allometric equations were constructed to estimate total biomass and carbon in the biomass which had an R2 aj (adjusted R square) greater than 94.5%. Finally, we compare our results to those that could have resulted from the use of default values, showing how site and species specific data contribute to the overall goal of improving carbon estimates and providing a more reliable account of the mitigation potential of forestry activities on climate change.